2004
DOI: 10.1055/s-0038-1632803
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the feline sacroiliac joint for lag screw fixation of sacroiliac fracture-luxation

Abstract: SummaryTwenty-eight feline pelves (56 hemipelves) were examined in order to identify the location for optimal sacroiliac screw placement in sacroiliac fracture-luxation repair. A drill hole was started on the median plane of the hemipelvis in the centre of the body of the first sacral segment until it penetrated the lateral cortex of the ilial wing, thus providing optimal drill hole placement. The position of the drill hole on the articular surface of the sacral wing and on the lateral surface of the ilial win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 5 publications
0
43
0
1
Order By: Relevance
“…Previous studies have reported the same landmark when defining safe corridors for lag screw placement in cats. 3,19 Burger et al 3 described the sacral tuber as the reference for drilling the screw hole. The sacral tuber is straightforward to visualise intraoperatively and is delimited by the cranial dorsal iliac spine and the caudal dorsal iliac spine.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have reported the same landmark when defining safe corridors for lag screw placement in cats. 3,19 Burger et al 3 described the sacral tuber as the reference for drilling the screw hole. The sacral tuber is straightforward to visualise intraoperatively and is delimited by the cranial dorsal iliac spine and the caudal dorsal iliac spine.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported the ventral gluteal line as an additional landmark, which can also be useful when choosing the pin placement start point. 3,19 The distance between the DLVC-I is at its greatest at the most craniodorsal aspect of the iliac wing. Identifying this landmark guarantees the largest dorsoventral area to place the pin within the dHPC and avoids the vertebral canal ventrally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations